Cover Feature: Robust Hydrogenation of Nitrile and Nitro Groups to Primary Amines Using Ni2P as a Catalyst and Ammonia Borane under Ambient Conditions (Asian J. Org. Chem. 11/2017). Issue 11 (30th October 2017) - Zen, Yun‐Feng; Fu, Zi‐Cheng; Liang, Fei; Xu, Yong; Yang, Dan‐Dan; Yang, Zhi; Gan, Xin; Lin, Zhe‐Shuai; Chen, Yong; Fu, Wen‐Fu
Abstract : Selective hydrogenation of nitrile groups to primary amines is challenging owing to their high reactivity towards producing secondary and tertiary amines. An unprecedented and efficient system for the hydrogenation of nitrile and nitro groups to primary amines catalyzed by Ni2 P nanoparticles in mixed aqueous H3 NBH3 solution under ambient conditions is reported. The system exhibits high catalytic selectivity towards generating primary amines, resulting in good isolated yields. Density functional theory calculations rationalize the observed results that composite interactions among species on the catalyst surface alter the catalytic pathway. More information can be found in the Communication by Wen‐Fu Fu et al. onpage 1589 in Issue 11, 2017 (DOI:10.1002/ajoc.201700383 ).